Boerhaave Syndrome - A Rare but Serious Esophageal Emergency - Szarek, Paula; Kołacz, Jakub; Oleś, Patrycja; Kwiatkowski, Marcin; Bochniak, Paulina (Quality in Sport, 2025)
Introduction: Boerhaave syndrome is a rare but serious cause of spontaneous esophageal rupture. It typically occurs after a sudden rise in pressure within the esophagus against a closed glottis, most often following severe vomiting. This full-thickness tear in the esophagus leads to a high risk of death, especially when there is a delay in diagnosis. The syndrome mainly impacts middle-aged men and often shows non-specific symptoms like chest pain, difficulty breathing, and subcutaneous emphysema, which can resemble cardiopulmonary emergencies. Quick identification remains challenging because of its rarity and varied clinical signs. Aim of the Study: This review aims to provide a comprehensive overview of the syndrome’s definition, pathophysiology, clinical characteristics, diagnostic algorithms, and current therapeutic strategies, emphasizing the pivotal role of early intervention in reducing morbidity and mortality. Materials and Methods: A literature review was conducted using databases such as Google Scholar and PubMed with search terms including "Boerhaave syndrome”, “spontaneous esophageal rupture”, “gastrointestinal emergencies”, “esophageal trauma”. Conclusions: Boerhaave syndrome requires quick diagnosis and treatment to prevent death. Computed Tomography (CT) with contrast and esophagography can help detect it early, but only if used immediately. Prompt treatment within 12 to 24 hours and strong teamwork among doctors from different specialties greatly improve the patient’s chances of survival.